Imaging with ultrasound in physical therapy: What is the PT`s scope of practice? A competency-based educational model and training recommendations - Whittaker, J. L.; Ellis, R.; Hodges, P. W.; OSullivan, C.; Hides, J.; Fernandez-Carnero, S.; Arias-Buria, J. L.; Teyhen, D. S.; Stokes, M. J. (British Journal of Sports Medicine, 2019)
Physical therapists employ ultrasound (US) imaging technology for a broad range of clinical and research purposes. Despite this, few physical therapy regulatory bodies guide the use of US imaging, and there are limited continuing education opportunities for physical therapists to become proficient in using US within their professional scope of practice. Here, we (i) outline the current status of US use by physical therapists; (ii) define and describe four broad categories of physical therapy US applications (ie, rehabilitation, diagnostic, intervention and research US); (iii) discuss how US use relates to the scope of high value physical therapy practice and (iv) propose a broad framework for a competency-based education model for training physical therapists in US. This paper only discusses US imaging—not `therapeutic` US. Thus, `imaging` is implicit anywhere the term `ultrasound` is used.